Metastatic Pulmonary Adenocarcinoma 6 Years After Curative Resection for Ampullary Adenocarcinoma. Metastatic Disease from Initial Primary or Metachronous Tumour? - Giakoustidis, Alexandros; Cherian, P Thomas; Zen, Yoh; Jassem, Wayel; Prachalias, Andreas; Srinivasan, Parthi; Heaton, Nigel D; Rela, Mohamed (JOP. Journal of the Pancreas, 2011)
Context With patients surviving longer after pancreatic resection, the challenges now is the management of the unresolved longer-term issues. Case report A 53-year-old woman with painless obstructive jaundice, underwent a pylorous preserving pancreaticoduodenectomy for a pT3N0M0 ampullary adenocarcinoma in 2001 (patchy chronic pancreatitis with mucinous metaplasia of background pancreatic duct epithelium and acinar atrophy were noted). Despite adjuvant chemotherapy, at month 54 she required a pulmonary wedge resection for metastatic adenocarcinoma, followed by a pulmonary relapse at 76 months when she underwent 6 neoadjuvant cycles of gemcitabine/capecitabine and a left pneumonectomy. Finally 7 years after the initial Whipple’s, a single 18F fluorodeoxyglucose (FDG) avid pancreatic tail lesion led to completion pancreatectomy for a well-differentiated ductal adenocarcinoma with clear resection margins albeit peripancreatic adipose tissue infiltration. On review all resected tumour cells had identical immunophenotype (CK7+/CK20-/MUC1+/MUC2-) as that of the primary. She is currently asymptomatic on follow-up. Conclusions These findings suggest that in selected cases even in the presence of pulmonary metastasis, repeat resections could result in long-term survival of patients with metachronous ampullary cancer. Second, even ampullary tumours maybe should be regarded as index tumors in the presence of ductal precursor lesions in the resection specimen. Three distant metastases, particularly if long after the initial tumour, should instigate a search for metachronous tumour, especially in the presence of field change in the initial specimen. Risk-adapted follow-up protocols with recognition of such factors could result in cost-effective surveillance and potentially improved outcomes. Image: Histopathology of ampullary, lung, and pancreatic cancers.